2011
DOI: 10.1083/jcb.201007161
|View full text |Cite
|
Sign up to set email alerts
|

The frontotemporal dementia mutation R406W blocks tau’s interaction with the membrane in an annexin A2–dependent manner

Abstract: The R406W mutation prevents tau from functioning as a linker between the membrane and the microtubule cytoskeleton.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
118
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 122 publications
(119 citation statements)
references
References 51 publications
1
118
0
Order By: Relevance
“…In contrast, human tau overexpression from the GAL1/10 promoter in yeast, which lacks an endogenous tau homolog, does not produce any detectable phenotype in logarithmically growing wild-type cells [23,66]. Yet, it has been reported that co-expression with the gene encoding synuclein aggravates the toxic effects of overexpression of the latter [88].…”
Section: Tau Expression In Saccharomyces Cerevisiae and Merits Of Klumentioning
confidence: 89%
See 3 more Smart Citations
“…In contrast, human tau overexpression from the GAL1/10 promoter in yeast, which lacks an endogenous tau homolog, does not produce any detectable phenotype in logarithmically growing wild-type cells [23,66]. Yet, it has been reported that co-expression with the gene encoding synuclein aggravates the toxic effects of overexpression of the latter [88].…”
Section: Tau Expression In Saccharomyces Cerevisiae and Merits Of Klumentioning
confidence: 89%
“…All these modifications may affect the interaction with more than 70 predicted tau binding partners [11], including the tyrosine kinase fyn, the membrane-associated protein annexin A2, and its effector protein phosphatase PP2A [66][67][68]. Despite this plethora of regulatory systems and interactions, knockout mice lacking a functional tau gene do not display severe defects in brain function or development [69], which suggests the presence of redundant and compensatory mechanims in vertebrates.…”
Section: Posttranslational Modifications Influencing Tau Toxicitymentioning
confidence: 99%
See 2 more Smart Citations
“…The proline-rich domain of Tau contains 7 PXXP motifs, through which Tau can bind to the SH3 domains of other proteins, such as the Src family tyrosine kinase, Fyn. Tau can also bind to cell membranes by means of its N-terminal region, probably through an interaction with the membrane lipid binding protein, Annexin A2 [10].…”
Section: The Microtubule-associated Protein Taumentioning
confidence: 99%